Comparative analysis of the results of implementation of the methodology of teaching technology development of physical fitness of students - future doctors. - Radzijevsky, Viktor (Journal of Education, Health and Sport, 2017)
The content of three stages of training of technologies of development of physical capacity is revealed. The efficiency of the solution of the set tasks of the research by means of implementation of the methodology of teaching technology development of physical fitness of students - future doctors is shown. The proposed method of teaching the technologies of the development of physical fitness of students - future doctors aimed at the introduction of differentiated tasks, methods, forms and means aimed at the development of physical fitness of students, taking into account their physical preparedness, and provided for the unity of general and special training of students - future doctors for future professional activities. The proposed author’s technique envisaged three main stages of teaching technology of physical fitness development for students - future physicians. The initial stage of training was aimed at the development of general endurance, improvement of the functions of the cardiovascular and respiratory systems, strengthening the musculoskeletal system of students, which was achieved by the gradual retraction of the body into work, which was expressed in elongation of the running distance, walking while maintaining a uniform pace. At the second stage, students were offered exercises with an increase in the volume of loading in the mixed aerobic-anaerobic mode of energy supply in accordance with the state of health, physical and functional preparedness of students, while applying a continuous unified work in the form of cross-country running, paced Scandinavian walking in a wide range speeds, as well as continuous variable work, while turning to circular training. In the third stage, if students had a good level of physical fitness, we continued to increase gradually not only the amount of training loads, but also increased the intensity of exercises. But in most cases, when the increased requirements to the level of development of endurance conditions of professional activity were not presented and taking into account the low level of physical fitness of students, we kept the achieved level of mastered levels of training loads.